Nikoulabasis dalingarum, sp. nov. from Fiji (Odonata: Coenagrionidae) - Marinov, Milen; Donnelly, Thomas W.; Beatty, Christopher D. (Zootaxa, 2025)
Nikoulabasis dalingarum sp. nov. (holotype male, Viti Levu, Fiji) is erected as a new taxon. Illustrations of key characters and a distribution map are provided.